The potential of Sumbawa Honey (Apis dorsata) As a Natural Antioxidant - Yumni, Gharsina Ghaisani; Listiana, Fina; Sari, Septi Puspita; Nadhiroh, Siti; Sumantri, Sumantri (Universitas Ahmad Dahlan, 2023)
Honey is a natural ingredient that Indonesian people widely use to maintain a healthy body. One of the benefits of honey is as an antioxidant. This antioxidant activity is influenced by the producing bee, the source plant, and the producing area. This study aims to determine the antioxidant activity of Sumbawa honey originating from NTT. Honey samples were collected and dried using the freeze-drying method and then macerated with 70% ethanol. The viscous extract obtained was then fractionated using a liquid-liquid extraction method using n-hexane, ethyl acetate and ethanol-water as solvents so that the n-hexane (NF), ethyl acetate (EF) and water (WF) fractions were obtained. Each sample was tested for its antioxidant activity using the ABTS method with Trolox as a comparison. The results obtained were ethanol extract, NF, EF and AF had IC50 values respectively 96.054; 106,953; 70,206; and 101,649 g/ml. That indicates that the ethyl acetate fraction has a higher antioxidant activity than other solvents.